Phytochemicals Screening and Antibacterial Activity of Teijsmaniadendron Holrungii from West Papua - Sabir Sumarna; Muhammad Fajar Islam; Aslan Irunsah; Maria J. Sadsoeitoeboen; Kornela Irianti Mandatjan (TECHNO: JURNAL PENELITIAN, 2023)
Papua is an island with the highest flora biodiversity in the world. To date, the phytochemical content and antibacterial bioactivity of the Teijsmaniadendron holrungii plant from West Papua have never been reported. In this study, phytochemical screening and bioactivity tests of T. holrungii bark ethanol extract against E. coli and S. aureus bacteria were carried out. The results showed that T. holrungii bark ethanol extract contained alkaloids, flavonoids, steroids, and tannins. The inhibitory activity of bacterial growth increased with an increase in concentrations (w/v) of 5; 10; 20; 40; and 80%, with inhibitory zones of 14.5; 17; 18; 20; and 22 mm for E. coli bacteria and 4.5; 5.5; 6; 7.5; and 9.5 mm for S. aureus bacteria.